Fish mortality associated to volcanic eruptions in the Canary Islands - Caballero, María José; Perez-Torrado, Francisco José; Velázquez-Wallraf, Alicia; Betancor, Mónica Beatriz; Fernández, Antonio; Castro-Alonso, Ayoze (Frontiers in Marine Science, 2023)
The Canary Islands are an active volcanic archipelago. In the last decade, volcanic activity has occurred twice on the youngest and western most islands: El Hierro (submarine eruption) in 2011-12, and La Palma (subaerial eruption) in 2021. 70 fish specimens of different species from El Hierro volcano and 14 from La Palma were necropsied. A notable high and early mortality of fishes was registered during the submarine eruption of El Hierro. In most of them, generalized congestion in the gills, liver, spleen, kidney, heart and rete mirabile of the swim bladder was observed. Some specimens also presented exophthalmia, gastric eversion, ocular haemorrhages, over-inflation of swim bladder and gas bubbles mainly on the skin and cornea. The eruption of La Palma volcano was characterized by the emission of large amounts of lava flows and pyroclastic deposits (mainly ash in size) both, on land and sea. Lava flowed on land and eventually reached the sea, forming lava deltas in the coastline of La Palma. This event was also associated with an increase in fish mortality in locations near to the lava deltas. Fishes presented ash particles in opercula/oral cavities and gills. In addition, several fishes presented an intense intestinal impaction composed of volcanic material including ashes and hyaloclastites fragments. To our best knowledge this study describes, for the first time, pathological findings in dead fishes associated with two different styles of recent volcanic eruptions in the Canary Islands.